2019
DOI: 10.3390/nano9101414
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Inscribed Stress-Induced Birefringence of Sapphire

Abstract: Birefringence of 3×10−3 is demonstrated inside cross-sectional regions of 100 μm, inscribed by axially stretched Bessel-beam-like fs-laser pulses along the c-axis inside sapphire. A high birefringence and retardance of λ/4 at mid-visible spectral range (green) can be achieved using stretched beams with axial extension of 30–40 μm. Chosen conditions of laser-writing ensure that there are no formations of self-organized nano-gratings. This method can be adopted for creation of polarization optical elements and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…6(b) show negative slope which corresponds to the ∆n = −0.45 for the d = 200 nm height of the b-Si. This is an extraordinarily high value and the negative sign is consistent with the form-birefringence of b-Si, which is negative by definition 24 . This birefringence caused a phase change of ∼ 6 − 7% of the wavelength across the full visible spectrum.…”
Section: Quantitative Measurement Of Birefringence In Reflectionsupporting
confidence: 57%
See 1 more Smart Citation
“…6(b) show negative slope which corresponds to the ∆n = −0.45 for the d = 200 nm height of the b-Si. This is an extraordinarily high value and the negative sign is consistent with the form-birefringence of b-Si, which is negative by definition 24 . This birefringence caused a phase change of ∼ 6 − 7% of the wavelength across the full visible spectrum.…”
Section: Quantitative Measurement Of Birefringence In Reflectionsupporting
confidence: 57%
“…4). Color changes indicated presence of birefringence even larger than that observed in the laser-inscribed sapphire where the length of stressed volume was d ≈ 40 µm and ∆n ∝ 10 −4 [25]. Here, d = 0.2 µm and proportionally higher birefringence is expected for the same retardance ∆n × d (the same color on the Michel-Levy chart).…”
Section: Birefringence Of Tilted B-simentioning
confidence: 62%
“…The demonstrated demagnification of Bessel beam down to diameter 2w 0 = 1 µm is favorable to exceed the required irradiance of I p ≡ E p /(t p × πw 2 0 ) = 10 TW/cm 2 for dielectric breakdown of dielectrics (sapphire [28], olivine [29], silica [30] and glasses [31]) by only E p = 8 nJ (on target) pulses of t p = 100 fs duration for Gaussian beam and about E p ≈ 20 µJ for the entire length of the Bessel pulse for discussed here holey-axicon. Tight focusing of fs-Bessel pulses into focal spot with lateral cross section ∼ λ well defines the axial modification inside, e.g., crystalline sapphire [32], without formation of nanogratings and confines structural modification directly along optical axis.…”
Section: Fabrication Of Holey-axiconmentioning
confidence: 99%
“…Structural defects induced by nanograting formation in silica can be thermally annealed without change to their form-birefringence [20] and temperatures up to 1150 • C (for 3 hours) were used for silica without erasing optical memory bits [78]. Nanogratings can also be recorded in crystalline sapphire, which has an even broader spectral window of transmission into the IR spectral range as compared to silica, and a very high (metal-like) thermal conductivity [79]. It was shown that instead of self-organised formation of nanogratings, form-birefringence of ∆n ≈ 3 × 10 −3 can be inscribed in a deterministic way down to 100 nm periods in sapphire [79].…”
Section: Outlook For Fs-laser Produced Micro-optics: Instrumentation ...mentioning
confidence: 99%
“…К другому виду структур, обладающих двулучепреломлением, следует отнести микроструктуры на основе микролиний в кристаллах сапфира [6], в этом случае двулучепреломление формировалось вследствие механических напряжений внутри области, не подвергавшейся лазерной обработке. Двулучепреломляющая структура в сапфире действует как одноосный отрицательный кристалл.…”
unclassified